Digest: A lizard evolutionary history illustrates a past Neotropical dispersal route* - Weisenberg, Erick Willy [UNESP]; Mori, Gustavo Maruyama [UNESP] (Oxford University Press (OUP), 2020)
Extensive lineage interchanges among Neotropical biomes are key to understanding their remarkable biodiversity. At a population level, one could expect to observe past cross-regional connections. The description of the phylogeographic history of a forest-associated lizard by Ledo et al. (2020) revealed a likely interbiome dispersal route through networks of riparian forests surrounded by dry habitats. We anticipate that future studies focusing on understudied widespread organisms like plants will build on these findings to better describe the origins of Neotropical diversity.